1995
DOI: 10.1164/ajrccm.152.5.7582282
|View full text |Cite
|
Sign up to set email alerts
|

Rhinovirus inhalation causes long-lasting excessive airway narrowing in response to methacholine in asthmatic subjects in vivo.

Abstract: Exacerbations of asthma are often associated with respiratory infections, and particularly those caused by rhinovirus. The causative role of rhinovirus in these acute episodes is still unclear, since it has not been determined whether or not infection with the virus promotes excessive airway narrowing in asthma. We tested the hypothesis that experimental infection with inhaled wild-type rhinovirus 16 (RV16) increases the maximal degree of airway narrowing in response to bronchoconstrictor stimuli in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
113
2
8

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(134 citation statements)
references
References 28 publications
11
113
2
8
Order By: Relevance
“…2b; r ϭ 0.79, P ϭ 0.01), but none in normal subjects. There was also a strong significant inverse correlation between the change in PC 20 and virus load in the asthmatic group ( Fig. 2d; r ϭ Ϫ0.77, P ϭ 0.016).…”
Section: Rv Induced Reductions In Lung Functionmentioning
confidence: 80%
See 1 more Smart Citation
“…2b; r ϭ 0.79, P ϭ 0.01), but none in normal subjects. There was also a strong significant inverse correlation between the change in PC 20 and virus load in the asthmatic group ( Fig. 2d; r ϭ Ϫ0.77, P ϭ 0.016).…”
Section: Rv Induced Reductions In Lung Functionmentioning
confidence: 80%
“…Human experimental RV infection in mild asthmatic volunteers report RV infection is associated with augmented physiological and inflammatory responses to allergen challenge (16, 17) and reductions in PEF (18), forced expiratory volume in 1 s (FEV 1 ) (19), and increases in bronchial hyperreactivity (20). However, studies that have investigated both asthmatic and normal subjects have not demonstrated differences between subject groups in reductions in lung function or lower airway inflammatory responses (21,22).…”
mentioning
confidence: 99%
“…It is tempting to propose that acute viral infection among patient would precipitate increased sinus changes and an exacerbation of asthma. [23][24][25] Further understanding of the relationship between sinus disease and exacerbations of asthma will need prospective studies in which the change in sinus CT at the time of an attack can be related to evidence of viral infection, allergen exposure, and inflammation. However, the problem will remain difficult to resolve without better understanding of the immunologic mechanisms that lead to persistent eosinophil-rich inflammation in the sinuses.…”
Section: Discussionmentioning
confidence: 99%
“…The increased airway reactivity demonstrated in experimental rhinovirus infections in asthmatic subjects (9,10) and atopic subjects (11) and the induction by rhinovirus of late asthmatic responses to inhaled allergen (8,11) also provide indirect evidence of a link between lower respiratory inflammation during rhinovirus experimental infections and the mechanisms of virus-induced asthma exacerbations. Finally, evidence that the lymphocytic and eosinophilic inflammation observed during rhinovirus experimental infections (7)(8)(9) is probably also an important mechanism involved in virus-induced asthma exacerbations comes from the fact that asthma exacerbations have been induced by experimental rhinovirus infections (9,12).…”
mentioning
confidence: 99%